Ghost soldier [compact disc, unabridged] - Cussler, Clive; Maden, Mike (Cussler, Clive. Oregon files adventures., 2024)
When African jihadis attack a Nigerian regiment using American weapons, Cabrillo and the Oregon crew are on the case, investigating from Afghanistan to Kuala Lumpur to track a mysterious arms dealer-a genius, or perhaps a devil, known only as the Vendor. Cabrillo goes undercover to find the Vendor's base, but his adversary isn't just an arms smuggler. He's an arms maker, and Cabrillo just walked into a lethal military game alongside the most dangerous mercenaries in the world, designed to test the Vendor's cutting-edge AI arsenal. And yet, surviving an arena full of flame-throwing robots isn't even his biggest problem. The Vendor has an army of high-speed drones headed for a pivotal military site, and if the Oregon crew can't stop them from releasing a deadly neurotoxin, the entire globe will erupt in conflict.